Autoperception of Health, Quality of life and Psychological Well-being in a sample of major - Benavente Cuesta, María Hinojal; Quevedo Aguado, María Paz (Revista Española de Comunicación en Salud, 2019)
WHO (2015) states that there is an increase in ageing in the world population, which is further compounded by situations of age discrimination. These negative attitudes constitute entrenched stereotypes that harm not only society but also the elderly themselves. For this reason, all social and health actors need to work under the paradigm of Active Ageing, which advocates an integrated old age in a context of development and social participation. Objectives: To analyse the health self perception, quality of life and psychological welfare of the elderly, as well as to compare whether there are differences in relation to sex, place of residence (urban/rural) and how to perceive retirement. Methodology: Sample: 91 subjects (=74,07 years).Instruments: Health Questionnaire SF (36) and Psychological Welfare Scale (Díaz et al., 2006). Results: The participants show a very satisfactory assessment in their own perception of health and quality of life. In this respect, different trends are observed according to habitat, rural/urban, where the largest resides. On the other hand, there are also differences in the dimensions of psychological welfare according to the sex of the subjects and the way they perceive the fact of retirement.
Keywords: Autoperception of health; Quality of life; Psychological Well-being; Aging; Active Aging; Oldness